Strategi reimajinasi gerakan ikatan pelajar muhammadiyah jawa tengah menuju generasi pelajar berdampak - Ananta, Radite Ranggi; Ikhwan Adriansyah; Muhammad Nasir; Tria Budi Septiani; Hanum Rahma Aini, (Indonesian Journal of Muhammadiyah Studies (IJMUS), 2025)
This article aims to analyze the reimagination strategy of the Muhammadiyah Student Association (IPM) movement in Central Java through the development of the Rumah Berkarya Pelajar (RBP) concept as an effort to shape a generation of impactful students. The background of this study stems from the structural and cultural challenges faced by IPM Central Java, such as program stagnation, weak cadre actualization, and the need to strengthen the movement’s relevance in addressing strategic contemporary issues. This research employs a qualitative descriptive approach combined with triangulation methods for data collection and analysis. The triangulation involves three main data collection techniques: questionnaires, in-depth interviews, and observation. Primary data were collected using purposive sampling, targeting 298 IPM cadres across Central Java and conducting in-depth interviews with the daily leadership of IPM Central Java. The study reveals that RBP functions as a strategic community space grounded in value integration, cadre ecosystem strengthening, and social impact orientation. RBP is constructed through a Theory of Change framework that incorporates nine fundamental movement values and the identity of the Pelajar Gayeng, further enhanced with an implementation roadmap and cross-sectoral collaborative strategies within IPM. This comprehensive strategy is expected to accelerate the transformation of IPM Central Java into a progressive, solution-oriented, and sustainable student movement.